DIVERSITY PATTERNS OF CARBONIFEROUS AND PERMIA RUGOSE CORALS IN SOUTH CHINA - Wang X.-D.; Wang X.-J.; Zhang F.; Zhang H. (My University, 2006)
The diversity and changing patterns of rugose corals in the Carboniferous and Permian of South China are analysed by statistical analyses of 45 families, 284 genera, and 1979 species from 14 consecutive time intervals. The ancestors of Carboniferous rugose corals originated early and underwent preliminary radiation in the late Famennian, but were eliminated by the Hangenberg global regressive event, which marks the Devonian - Carboniferous boundary. Radiation of typical Carboniferous rugose corals began in the late Tournaisian, when they were represented by an abundance of columellate taxa such as Kueichouphyllum and a significant diversification of Keyserlingophyllum. A decrease in the diversity of rugose genera occurred in the Serpukhovian, followed by a change in the composition of the rugose coral assemblages at the Mid-Carboniferous Serpukhovian - Bashkirian boundary, where large dissepimented taxa with complex axial structures disappeared. In the Bashkirian the Serpukhovian taxa were replaced by compound rugosan taxa of the Geyerophyllidae, Kepingophyllidae and Waagenophyllidae. This compositional change was associated with a global regressive event, recognized in South China by the absence of upper Serpukhovian strata in many places and by several erosional surfaces in carbonate sequences in the Lower Yangtze region. This regressive event was probably caused by an episode of glaciation in Gondwana. Subsequent transgression occurred in South China during the early Bashkirian, where a wide, uniform shallow-water platform developed in South China, on which were deposited tidal-flat dolostone and pure limestone containing compound rugose corals. Another change in the rugose coral assemblages, at the Sakmarian-Artinskian boundary, resulted in the absence from the Artinskian of representatives of typical Pennsylvanian and Early Permian families such as the Bothrophyllidae, Lithostrotionidae, Cyathopsidae, and Petalaxidae. Families uniquely typical of the Permian, characterized by Waagenophyllidae and Kepingophyllidae, dominate post-Sakmarian strata. This faunal change may be related to a major, worldwide regression, recognized at the end of the Sakmarian. Extinction of rugose corals at the end of the Permian occurred in two phases in South China. The first phase occurred at the end of the Capitanian and eliminated 47% of the families and 45% of the genera. Extrusion of the Omeishan Basalt, which is widely distributed in the western part of South China, and/or a global regression at the end of the Guadalupian could be the principal causes of this first phase of mass extinction. The second phase, which occurred at the end of the Changhsingian and is the largest extinction event in Earth's history, eliminated all remaining rugose corals. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: CARBONIFEROUS; DIVERSITY PATTERNS; PERMIAN; RUGOSE CORALS; SOUTH CHINA; Paleozoic::Carboniferous; Палеозой::Каменноугольная